Evaluation of strong anion exchange hyper-crosslinked resin for lanthanum removal - Aimi Asyiqin, Abu Kassim; Norhayati, Abdullah; Nur Izziana, Ishak (IOP Publishing, 2020)
In this study, strong anion exchange hyper-crosslinked resin was used for the removal of rare earth element, lanthanum. Poly (styrene-co-EDGMA-co-VBC) is a resin that was synthesized and used in this research. The objective of this research is to study the pH stability and to evaluate the resin for lanthanum removal by using the Solid Phase Extraction (SPE) batch method where the influent of lanthanum solution will be loaded to the designed column containing resin. The pH stability test of resin was studied at different pH (pH 2-5). The evaluation of resin for resin loading (0.5, 1.0, and 1.5 g) and concentration of lanthanum (10, 30, and 50 ppm) were investigated. From the experiment, the resin is stable in acid solution since there is no change in the functional group. The morphology surface using Scanning Electron Microscope (SEM) shows a rough surface and beads attach on the resin without porous on the surface of resin except the resin at the condition of 50 ppm of with 1.0g resin. The resin that performed at 50 ppm with 1.0 g was successful remove lanthanum for 26.7 ppm based on ICP-MS analysis. As a conclusion, this resin can be used for removal of lanthanum.